2015
DOI: 10.1007/s10863-015-9600-5
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation in brain or spinal cord mitochondria after injury

Abstract: Extensive evidence has demonstrated an important role of oxygen radical formation (i.e. oxidative stress) as a mediator of the secondary injury process that occurs following primary mechanical injury to the brain or spinal cord. The predominant form of oxygen radical-induced oxidative damage that occurs in injured nervous tissue is lipid peroxidation (LP). Much of the oxidative stress in injured nerve cells initially begins in mitochondria via the generation of the reactive nitrogen species peroxynitrite (PN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 41 publications
(61 reference statements)
0
71
0
1
Order By: Relevance
“…SKY sonrası nörolojik hasar 'primer mekanik yaralanma' ile olduğu kadar doku hasarına yol açan hücre ölümü aktivasyon kaskatlarından da (sekonder yaralanma) kaynaklanmaktadır (32). Sekonder omurilik yaralanması; oluşan primer yaralanmanın başlattığı ve yaralanmadan sonraki saatler ve günler içerisinde gelişen bir dizi patofizyolojik sürece bağlı olarak ortaya çıkan hasardır (33)(34)(35). Birçok deneysel çalışma, doza bağlı olarak yaralanmanın ciddiyetiyle değişmekle birlikte omurilik kan akımında azalma ve yaralanmadan sonra zamanla kötüleşen bir omurilik kan akımı azalması olduğunu göstermiştir (36).…”
Section: Discussionunclassified
“…SKY sonrası nörolojik hasar 'primer mekanik yaralanma' ile olduğu kadar doku hasarına yol açan hücre ölümü aktivasyon kaskatlarından da (sekonder yaralanma) kaynaklanmaktadır (32). Sekonder omurilik yaralanması; oluşan primer yaralanmanın başlattığı ve yaralanmadan sonraki saatler ve günler içerisinde gelişen bir dizi patofizyolojik sürece bağlı olarak ortaya çıkan hasardır (33)(34)(35). Birçok deneysel çalışma, doza bağlı olarak yaralanmanın ciddiyetiyle değişmekle birlikte omurilik kan akımında azalma ve yaralanmadan sonra zamanla kötüleşen bir omurilik kan akımı azalması olduğunu göstermiştir (36).…”
Section: Discussionunclassified
“…A short therapeutic window is one significant limitation of the aforementioned indirect mechanisms. Multiple studies have reported near instantaneous increases in ROS production after SCI (Liu et al, 1998Bao and Liu, 2004;Xiong et al, 2007), which means that pharmacological agents would need to be administered immediately to ensure that they are able to act and interfere with the initial "burst" of free radical production that occurs after SCI (Hall, 2011;Bains and Hall, 2012;Hall et al, 2016).…”
Section: Mitochondrial-based Treatmentmentioning
confidence: 99%
“…Although there have been promising preliminary studies investigating the efficacy of NACA, NIM811, Mdivi-1, and mitochondrial-targeted antioxidants, there remains a great deal of work to be done with these compounds and, as is often the case, there is no guarantee that the results observed in animals will translate to humans. Hall et al (2016) suggested that combinatorial therapies could address the obvious deficit in treatment, as pursuing a single facet of the mitochondrial dysfunction-induced damage that occurs after SCI may not be enough to produce effective neuroprotection. An alternate method of targeting multiple aspects of mitochondrial function that has not yet been effectively explored for the treatment of SCI is pharmacological enhancement of mitochondrial biogenesis (MB).…”
Section: Mitochondrial Biogenesismentioning
confidence: 99%
See 2 more Smart Citations